Kobiety w polskiej administracji publicznej - Klejdysz, Natalia (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The amendments made to the electoral law, and effective as of 2011, introduced a quota system but they did not solve the problem of women’s participation in public life. Each sex was guaranteed a minimum of 35% of seats on electoral lists, without the requirement of alternating the candidates of different sexes, allowing certain political parties to only appear to implement the legislation. Despite the legal regulation imposing a requirement to increase the number of female candidates on electoral lists, the number of women currently in parliament increased only marginally, which raises the question of the degree of women’s participation in those executive organs of the state which are not required to observe a quota. There is much to be desired as regards the participation of women in the organs of state administration at both central and local levels in Poland. Political posts are clearly dominated by men. As regards administrative positions, the proportion of women depends on the degree of power connected with them: the higher the level in the hierarchy, the fewer women there are. As concerns‘executive’ posts, we can talk not only about a balance of sexes, but even about the prevalence of women, in some cases. Therefore, it is increasingly often postulated in public debate to introduce a quota system into the organs of state administration, the more so as some European countries have already applied similar solutions.